Prostitution and «unfreedom» in the Interwar era - Τζανάκη Δήμητρα (The Greek Review of Social Research, 2018)
With the present article, I intend to show how during the interwar period, a medical discourse was gradually created, aiming at the physical and ethical «sofronismos» (disciplinary correction) of the population. By trying to make it clear how within this framework the body of the ‘common woman’ was used by the state with the aid of science for the introduction of biopower/biopolitics control mechanism to the population on the pretext of protecting society from aphrodisiac transmitted diseases. It is at this very point that a «truth of danger» was actually established, which even persuaded the feminist movements of the time for the incompatibility of «freeness» in a civilized society.